Pengaruh Perhatian dan Tingkat Pendapatan Orang Tua terhadap Hasil Belajar Ekonomi Siswa Kelas XI di SMA Negeri 12 Sijunjung. - Darnis, Asli; Ansofino, Ansofino; Ramayani, Citra (Pendidikan Ekonomi, 2013)
ABSTRACT The purpose of this study was to observe the effect of parental income and parental level on learning outcomes in economy class XI SMA 12 Sijunjung school year 2012/2013 . This type of research is quantitative . The population in this study were all students of class XI in SMA 12 Sijunjung many as 49 people . The instrument used in this study was a questionnaire . Data analysis is used in two ways : 1 ) descriptive analysis , and 2 ) inductive analysis. The results showed that : the first concern of parents of learning outcomes in economy class XI SMA 12 Sijunjung significantly to the value of t_ ( count ) > t_tabel ie 3.217 > 2.021 , and sig 0.002 < 0.05 then Ho is rejected and Ha accepted . The second level of parental income on learning outcomes economy class XI student at SMAN 12 Sijunjung significantly to the value of t_ ( count ) > t_tabel ie 7.609 > 2.021 , and sig 0.000 < 0.05 then Ho is rejected and Ha accepted . The third concern and income level of parents of learning outcomes in the economy class XI SMA 12 Sijunjung significantly to the value of F_ ( count ) > F_ ( table ) is 39.276 > 3.23 and sig 0.000 < 0.05 then Ho is rejected and Ha accepted . Contributions of attention and income of parents of the results of the economic study in class XI Sijunjung SMA 12 is 0.631 or 63.1 %. Parental concern and the level of parental income is an important factor that can affect student learning outcomes in economic subjects . Contribution of this study is that parents pay more attention to their children about the issue kependidikannya , in order to increase student learning outcomes. Keywords : Attention Effect , Income Parents , Student Learning Outcomes.